Stream nitrogen concentration, but not plant N‐fixing capacity, modulates litter diversity effects on decomposition. (1st March 2017) - Tonin, Alan M.; Boyero, Luz; Monroy, Silvia; Basaguren, Ana; Pérez, Javier; Pearson, Richard G.; Cardinale, Bradley J.; Gonçalves, José Francisco; Pozo, Jesús
Summary: We are facing major biodiversity loss and there is evidence that such loss can alter ecosystem functioning. However, the effects of plant diversity on decomposition – a key component of the global carbon cycle – are still unclear. A recent study suggested that a plant trait – their nitrogen (N)‐fixing capacity – could mediate effects of litter diversity on decomposition by means of a microbial transfer of N from N‐fixers to non‐fixers. We explored this possibility in a microcosm experiment in which we manipulated litter species richness (one, two or four species), N‐fixing capacity (N‐fixer or non‐fixer species), the presence of detritivores ( Sericostoma pyrenaicum larvae present or absent) and water N concentration [natural stream water (0·366 mg L −1 of NO3 ‐N) or elevated N concentration (five times the natural concentration: 1·835 mg L −1 )]. We show that litter diversity accelerated decomposition by micro‐organisms and detritivores (by 7% and 15% respectively), mostly through complementarity effects. However, enhanced decomposition did not result in higher detritivore growth, possibly because all litter combinations provided sufficient resources for their maximum growth. The plant N‐fixing capacity had no effect on decomposition, which varied among species most likely because of differences in a combination of litter traits. Detritivores maximized the consumption of their preferred resource in litter mixtures, but also exploited less preferred resources, and their C : N ratios increased during the experiment regardless of litter type or water N concentration. Microbial decomposition of litter with low N content was enhanced at elevated water N concentration, suggesting that micro‐organisms used nutrients from the water when those nutrients were limiting in leaf litter. In contrast, detritivore growth was impaired at elevated water N concentration, possibly because a stoichiometric imbalance entails metabolic costs. Our findings suggest that loss of plant diversity in riparian forests would mostly affect decomposition in streams of high nutrient status, where effects on microbial decomposition would be more evident and detritivore populations may be reduced. A lay summary is available for this article. Abstract : Lay Summary